ABC of epilepsy - Smithson, Henry; Walker, M. C. (Matthew Charles); ebrary, Inc. (Chichester, West Sussex, U.K. : John Wiley & Sons, 2012)
"This practical guide to the classification and diagnosis of epilepsy provides coverage of what epilepsy is, how to make the diagnosis, anti-epileptic drugs, nondrug treatments, and living with epilepsy. Richly illustrated, the book will also address epilepsy within special groups such as women, children and those with learning disabilities, as well as providing guidance on long term monitoring and review, and support and self-management. Written for GPs and related primary health care professionals, this book reflects current NICE guidelines"--Provided by publisher.
Machine generated contents note: What is epilepsy? Incidence, prevalence and aetiology / Henry Smithson & Matthew Walker -- Describing and classifying the condition / Colin Ferrie & Matthew Walker -- Making the diagnosis - taking a history, clinical examination, investigations / Jan Bagshaw, Colin Ferrie, Mike Kerr -- Managing the drug treatment of epilepsy / Colin Ferrie ... [et al.] -- Non-drug treatments including epilepsy surgery / Colin Ferrie, Henry Smithson & Matthew Walker -- Prolonged or repeated seizures / Matthew Walker -- Special groups: women, children, learning disability and the elderly / Jan Bagshaw, Colin Ferrie & Mike Kerr -- Monitoring and review: how to manage the condition long term / Colin Ferrie, Alice Hanscomb & Mike Kerr -- Living with epilepsy: information, support and self management / Alice Hanscomb, Henry Smithson.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Epilepsy; Epilepsy -- Diagnosis; Epilepsy -- Treatment; Electronic books